KNOWLEDGE MANAGEMENT UNTUK CUSTOMER SERVICE - Sugandi, Lianna (Bina Nusantara University, 2010)
Knowledge is a success key in every field aspects. Along with the development in the world nowadays, where globalization is a challenge in every Indonesian human resource to face global competition. In this case, education has important part as media in developing qualified human resources and also as the place where they can be educated in their field. In the development of information technology, it came new systems in several fields including what educational field known as e-learning. Knowledge management (KM) is one implementation of e-learning. There is a concept that gathers all knowledge aspects in easily accessed file or document, and also in hardly accessed as knowledge and experience.Keywords: knowledge management, human resource, education